The Response of Magnesium, Silicon, and Calcium Isotopes to Rapidly Uplifting and Weathering Terrains: South Island, New Zealand - Pogge von Strandmann, Philip A. E.; Hendry, Katherine R.; Hatton, Jade E.; Robinson, Laura F. (Frontiers in Earth Science, 2019)
Silicate weathering is a dominant control on the natural carbon cycle. The supply of rock (e.g. via mountain uplift) has been proposed as a key weathering control, and suggested as the primary cause of Cenozoic cooling. However, this is ambiguous because of a lack of definitive weathering tracers. We use the isotopes of the major cations directly involved in the silicate weathering cycle: magnesium, silicon and calcium. Here we examine these isotope systems in rivers draining catchments with variable uplift rates (used as a proxy for exposure rates) from South Island, New Zealand. Overall, there is no trend between these isotope systems and uplift rates, which is in contrast to those of trace elements like lithium or uranium. Li and Si isotopes co-vary, but only in rapidly uplifting mountainous terrains with little vegetation. In floodplains, in contrast, vegetation further fractionates Si isotopes, decoupling the two tracers. In contrast, Mg and Ca isotopes (which are significantly affected by the weathering of both carbonates and silicates) exhibit no co-variation with each other, or any other weathering proxy. This suggests that lithology, secondary mineral formation and vegetation growth are causing variable fractionation, and decoupling the tracers from each other. Hence, in this context, the isotope ratios of the major cations are significantly less useful as weathering tracers than those of trace elements, which tend to have fewer fractionating processes.